Sexual and temporal variation in New Zealand bellbird song repertoires - Roper MM; Webb WH; Fukuzawa Y; Evans C; Harmer AMT; Brunton D (https://www.biorxiv.org/content/10.1101/2021.09.29.462458v1.article-info, 2021)
How song repertoires vary within species and change over time is well studied in male songbirds. However, variation in female song repertoires remains largely unstudied despite female song being much more common and complex than once assumed. We investigated the song syllable repertoire of the New Zealand bellbird ( Anthornis melanura ), a species where both sexes have complex but sexually dimorphic song. We compared songs at individual and population levels to investigate sex and temporal variation of syllable repertoires. We detected 96 syllable types in the population over four years, of which 58% were unique to males, 32% unique to females and 9% were shared between the sexes. The population syllable repertoire of both sexes changed substantially across years with similar turnover rates (Jaccard’s similarity coefficients; female 52.9–69.0%; male 58.6–73.7%). Furthermore, many syllable types, unique to each sex, varied in prevalence within the population across years. The syllable repertoire sizes of individuals were higher for males than females (13-32, n = 7 and 6-16, n = 8, respectively). Although these sample sizes were low, the temporal variation in syllable prevalence and turnover for individuals were similar to patterns at the population level. Overall, male and female bellbirds exhibited similarities in temporal patterns of yearly repertoire composition, with rapid changes in syllable prevalence, but females had fewer syllable types than males. We suggest that these similarities and differences are consistent with male and female song repertoires being driven by similar but not identical selection pressures.
Keywords: Female song; birdsong; syllable repertoire; songbird; bioacoustics